How Do Product Positioning and Consumer Knowledge of Green Brands Lead To Purchase Decisions? - Indah Fatmawati; Amudi, Nauval Al (School of Business, IPB University (SB-IPB), 2023)
Green branding has become a relevant strategy for winning the business competition. However, limited research has been conducted specifically investigating the role of green branding positioning on consumer green brand attitude and brand purchase. This study looks into the impact of green brand positioning on green purchasing decisions, considering consumer knowledge and consumer green brand attitude. Specifically, we examined how green brand positioning and knowledge form the green brand attitude and how green brand attitude determines green purchase decisions. Our research setting is green lamp purchase decisions. Respondents were green lamp purchasers and users, with a total sample size were 220 respondents. We developed several hypotheses and tested them using Structural Equation Modelling (SEM) with the AMOS 22. Our research findings showed that green brand positioning and knowledge positively and significantly impact consumers' green brand attitudes. Green brand attitude positively impacts green purchase decisions, and green brand positioning and knowledge positively and significantly affect a green purchase decision. In conclusion, our investigation showed that green brand positioning and green brand knowledge are essential for the formation of green brand attitudes and green brand purchase decisions. We also found the partial mediation of green brand attitude on the effect of green brand positioning on green brand purchase decisions. While for the impact of green brand knowledge on the green brand purchase decision, we did not find the mediating effects of green brand attitude. Keywords: green brand positioning, green brand knowledge, green brand attitude, green brand purchase decision